CpG oligodeoxynucleotide stimulates production of anti-neutrophil cytoplasmic antibodies in ANCA associated vasculitis - Sarvestani Ghafar; Patel Mittal; Nitschke Jodie; Jeffs Lisa; Hurtado Plinio R; Cassidy John; Hissaria Pravin; Gillis David; Au Peh Chen (BMC Immunology, 2008)
Abstract Background Wegener's Granulomatosis and Microscopic Polyangiitis are life-threatening systemic necrotizing vasculitides of unknown aetiology. The appearance of circulating antibodies to neutrophil cytoplasmic antigens (ANCA) is strongly associated with the development of the disease. A link between infection and disease has long been suspected, and the appearance of ANCA antibodies has been reported following bacterial and viral infections. The depletion of circulating B cells with monoclonal antibody therapy can induce remission, and this observation suggests a pathogenic role for B cells in this disease. As bacterial DNA is known to induce B cell proliferation and antibody production via TLR-9 stimulation, we have explored the possibility that unmethylated CpG oligodeoxynucleotide, as found in bacterial and viral DNA, may play a role in stimulating circulating autoreactive B cells to produce ANCA in patients with vasculitis. Results We have confirmed that unmethylated CpG oligonucleotide is a potent stimulator of antibody production by PBMC in vitro. The stimulation of PBMC with CpG oligonucleutides resulted in the production of similar amounts of IgG in both ANCA+ patients and normal controls. In spite of this, PR3 ANCA+ patients synthesised significantly higher amount of IgG ANCA than normal controls. In MPO ANCA+ patients, there was a tendency for patients to produce higher amount of ANCA than controls, however, the difference did not reach significance. Furthermore, we were able to detect circulating MPO-reactive B cells by ELISpot assay from the peripheral blood of 2 MPO+ ANCA vasculitis patients. Together, this indicates that circulating anti-neutrophil autoreactive B cells are present in ANCA+ vasculitis patients, and they are capable of producing antibodies in response to CpG stimulation. Of note, CpG also induced the production of the relevant autoantibodies in patients with other types of autoimmune diseases. Conclusion Circulating ANCA autoreactive B cells are present in patients with ANCA+ vasculitis. The production of ANCA from these cells in response to unmethylated CpG stimulation lead us to propose that stimulation of these cells by immunostimulatory DNA sequences such as CpG oligodeoxynucleotide during infection may provide a link between infection and ANCA associated vasculitis. This phenomenon may also apply to other antibody mediated autoimmune diseases.